FERMENTATION OF BIOETHANOL FROM THE BIOMASS HYDROLYZATE OF OIL PALM EMPTY FRUIT BUNCH USING SELECTED YEAST ISOLATES - Kusfanto, Hendriq Fauzan; Maggadani, Baitha Palanggatan; Suryadi, Herman (International Journal of Applied Pharmaceutics, 2017)
Objective: The purpose of this research was to investigate the potential of yeast-producing bioethanol from few type of grapes and durians. Methods: The isolation of potential yeast was carried out from five different types of fruits, namely, red grape, black grape, durian Medan, durian Bangkok, and durian Monthong. Optimum fermentation condition was obtained by comparing shaking and non-shaking, detoxifying the hydrolysate, varying temperature, and concentration of N source in the culture medium. Results: The results of an analysis using gas chromatography showed that the ideal conditions for the fermentation of bioethanol were at a temperature below room temperature (+220Â°C), without shaking, using the hydrolysate, without detoxification, and with a 1% concentration of ammonium acetate as a source of N. Among the isolates, isolate DM1 obtained from durian Medan showed a strong potential to produce bioethanol but at lower levels than Saccharomyces cerevisiae. The concentration of ethanol produced was 0.241%. Conclusion: A yeast isolate with a strong potential to produce bioethanol was discovered as the DM1, which isolated from Medanese durian. The isolate produced 0.241% bioethanol. However, fermentation optimization efforts using an oil palm empty fruit bunch hydrolysate substrate did not yield higher concentrations.